Regulating marine scientific research: a correlation between the law of the sea, science and national sovereignty - George, Mary (Malaysian Journal of Science, 2008)
This chapter argues that laws regulating marine scientific research have to be developed in Malaysia. The main argument in this Chapter is that it requires two sets of entities, namely the national scientists and the related competent scientific organizations on the one hand together with a sound institutional administrative mechanism on the other for the comprehensive development of the laws and procedure on marine scientific research for a state. The corpus juris of these regulations are derived from the provisions of the 1982 Law of the Sea Convention, the content of national legislation of states and the best practices as advocated by the United Nations as adopted by the Intergovernmental Oceanographic Commission. The existing Malaysian regulations on the subject should also be strengthened into a comprehensive national legislation. Hujah utama dalam bab ini adalah, dalam mengadakan perundangan sedemikian, peranan penting yang dimainkan oleh dua buah entiti tidak boleh diketepikan, iaitu, peranan para saintis kebangsaan dan badan -badan saintifik yang lain yang kompeten disertai dengan peranan badan pentadbiran yang sah dan berkesan bagi tujuan membangunkan perundangan dan prosedur berkenaan kajian saintifik marin di sebuah negara. Corpus juris perundangan tersebut didapati daripada peruntukan-peruntukan 1982 Law of the Sea Convention, kandungan perundangan pelbagai negara dan amalanamalan terbaik sepertimana yang dimajukan oleh Pertubuhan Bangsa-Bangsa Bersatu yang telah diterima pakai oleh badan Intergovernmental Oceanographic Commission. Peruntukan-peruntukan Malaysia yang sedia ada, juga dikehendaki diperkuatkan sebagai perundangan kebangsaan yang komprehensif.